2012
DOI: 10.1063/1.4717618
|View full text |Cite|
|
Sign up to set email alerts
|

Beyond power laws: A new approach for analyzing single molecule photoluminescence intermittency

Abstract: The photoluminescence intermittency (PI) exhibited by single emitters has been studied for over a decade. To date, the vast majority of PI analyses involve parsing the data into emissive and non-emissive events, constructing histograms of event durations, and fitting these histograms to either exponential or power law probability distributions functions (PDFs). Here, a new method for analyzing PI data is presented where the data are used directly to construct a cumulative distribution function (CDF), and maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
96
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(102 citation statements)
references
References 44 publications
6
96
0
Order By: Relevance
“…Our group recently analyzed the blinking of CdSe/CdS QDs with a total size of 4 nm and found deviations from linearity after the first decade in time, inconsistent with power-law statistics (Figure 3b). Together these studies suggest that for CdSe/CdS QDs of any size power-law statistics may not hold, calling into question the universality of power-law for QDs [56]. Further analysis on giant CdSe/CdS QDs with 1.9 nm cores and 3.5 monolayer shells have revealed that single exponential distributions are more appropriate for describing the durations of bright, gray and dark states [52].…”
Section: Photoluminescence Intermittency In Quantum Dotsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our group recently analyzed the blinking of CdSe/CdS QDs with a total size of 4 nm and found deviations from linearity after the first decade in time, inconsistent with power-law statistics (Figure 3b). Together these studies suggest that for CdSe/CdS QDs of any size power-law statistics may not hold, calling into question the universality of power-law for QDs [56]. Further analysis on giant CdSe/CdS QDs with 1.9 nm cores and 3.5 monolayer shells have revealed that single exponential distributions are more appropriate for describing the durations of bright, gray and dark states [52].…”
Section: Photoluminescence Intermittency In Quantum Dotsmentioning
confidence: 99%
“…In this study, the PI exhibited by VR in KAP and DKAP was analyzed using new statistical methods [56] to determine if the underling probability distribution functions describing the on - and off -durations were modified with isotopic substitution. This analysis involved the statistical comparison of complimentary cumulative distribution functions (CDFs) derived from the PI data obtained for VR in KAP and DKAP at three temperatures (23 °C, 45 °C, and 60 °C) [116].…”
Section: Photoluminescence Intermittency In Organic Luminophoresmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a widely shared theoretical interdisciplinary perspective, ranging from neurophysiology to sociology, from geophysics to economics, heavy tails and inverse power law distributions [2,3] are thought to be the signature of complexity. Of special interest are the scale-free distributions in time, for instance, the waiting time distributions of the "light on" and "light off" states of intermittent fluorescence in quantum dots [4][5][6][7], which has been proved [8,9] to be a renewal non-Poisson process. These scale-free waiting time distribution densities have the time-asymptotic form…”
Section: Introductionmentioning
confidence: 99%
“…The physics of blinking quantum dots (BQDs) [1][2][3][4] has generated a big interest but it is still a not yet fully understood phenomenon [2]. Analysis of the luminescence fluctuations led to the discovery [5,6] that these fluctuations are non-Poisson renewal processes.…”
Section: Introductionmentioning
confidence: 99%